Off-the-Vine Ripening of Tomato Fruit Causes Alteration in the Primary Metabolite Composition - Sorrequieta, Augusto (2013)
The influence of postharvest fruit ripening in the composition of metabolites, transcripts and enzymes in tomato (Solanum lycopersicum L.) is poorly understood. The goal of this work was to study the changes in the metabolite composition of the tomato fruit ripened off-the-vine using the cultivar Micro-Tom as model system. Proton nuclear magnetic resonance (1H NMR) was used for analysis of the metabolic profile of tomato fruits ripened on- and off-the-vine. Significant differences under both ripening conditions were observed principally in the contents of fructose, glucose, aspartate and glutamate. Transcript levels and enzyme activities of 　-amino butyrate transaminase (EC 2.6.1.19) and glutamate decarboxylase (EC 4.1.1.15) showed differences in fruits ripened under these two conditions. These data indicate that the contents of metabolites involved in primary metabolism, and conferring the palatable properties of fruits, are altered when fruits are ripened off-the-vine.